Chemical composition and microbial loads of chicken table eggs from retail markets in urban settings of Eastern Ethiopia (Journal of Advanced Veterinary and Animal Research, 2015)
For  the  determination  of  microbial  load,  chemical quality, pH and cholesterol level, a total of 400 table eggs  were  randomly  collected  from  10  retailers situated  at  major  urban  settings  in  Eastern  Ethiopia and Haramaya University Poultry Farm, Ethiopia. The data  were  analyzed  using  SAS.  High  moisture  and cholesterol  levels  and  low  pH  and  huge  microbial load  were  detected  in  the  eggs.  Exposure  of  eggs  to sunlight  in  the  market  and  transportation  of  eggs from  farm  to  the  retail  market  might  influence  in lowering  moisture  and  increasing  pH.  Huge microbial  contamination  of  eggs  from  retailers  at urban  settings  could  be  due  to  unhygienic  handling of  the  eggs,  lack  of  standard  storage  and transportation  facilities.  Storing  of  eggs  in refrigeration  condition  and  protection  of  direct  sun light  could  be  helpful  in  maintaining  quality  eggs. Introduction  of  refrigeration  systems  and construction  of  shades  in  markets  are  suggested  to maintain  and  improve  quality  of  eggs  sold  in markets. http://dx.doi.org/10.5455/javar.2015.b108